Self-inflicted injuries in adolescents and young adults: A longitudinal approach. - Sánchez-Teruel, David; Robles-Bello, María Auxiliadora; Camacho-Conde, José Antonio (Colegio Oficial de Psicólogos del Principado de Asturias, 2020)
Background: Suicide has become a major global public health problem in some clinical subpopulations. Adolescents and young adults with selfinfl icted injuries or non-suicidal self-harm appear to have been understudied. The aim of this study is to assess which socio-demographic and prior comorbid psychopathology condition variables in adolescents and young adults with self-infl icted lesions are likely to be more predictive of future self-injury after 12 months. Method: The eligible participants were 176 people (99 women and 77 men) aged 15-25 (mean = 20.3; SD = 4.56) who were subsequently divided into two groups (those who had been admitted again for self-infl icted injuries or non-suicidal self-harm (104; 59.1%), and those who had not (72; 40.9%) during the following 12 months. Results: The results obtained offer (i) a specifi c socio-demographic profi le in which women (OR [CI95%] = 6.22[6.03-7.11]) aged 21-22 (OR [CI95%] = 4.71[4.29- 5.73]) who are students (OR [CI95%] = 2.99 [1.58-6.01]) are likely to infl ict a new self-injury on themselves after 12 months, and (ii) a clear clinical profi le where several affl ictions are predictors of a new self-injury after 12 months. Conclusions: We discuss the urgent need to develop specifi c health protocols and improve public health alert measures for certain subpopulations.
Política de acceso abierto tomada de:https://www.psicothema.com/PublicationNorms2022.pdf
Keywords: Adolescentes - Psicología; Adolescentes - Conducta suicida; Suicidio - Etiología; Suicidio